Autosomal recessive polycystic kidney disease: case report of a newborn with rare PKHD1 mutation, rapid renal enlargement and early fatal outcome - Gregorio Serra (Italian Journal of Pediatrics, 2020)
Abstract Introduction Autosomal recessive polycystic kidney disease (ARPKD; MIM#263200) is one of the most frequent pediatric renal cystic diseases, with an incidence of 1:20,000. It is caused by mutations of the PKHD1 gene, on chromosome 6p12. The clinical spectrum is highly variable, ranging from late-onset milder forms to severe perinatal manifestations. The management of newborns with severe pulmonary insufficiency is challenging, and causes of early death are sepsis or respiratory failure. In cases of massive renal enlargement, early bilateral nephrectomy and peritoneal dialysis may reduce infant mortality. However, there is no conclusive data on the role of surgery, and decision-making is driven by patient’s clinical condition and expertise of the center. Patient presentation We hereby describe a preterm female newborn with perinatal, rapid and bilateral, abnormal growth of both kidneys, respiratory failure and initial signs of liver disease. She was subsequently confirmed to be affected by a rare and severe homozygous mutation of the PKHD1 gene, inherited from both her consanguineous parents. Our patient died 78 days after birth, due to a fungal sepsis which worsened her respiratory insufficiency. Conclusions This patient report shows some of the clinical and ethical issues of neonatal ARPKD, and the need of multidisciplinary approach and good communication with the family. Target next generation sequencing (NGS) techniques may guide and support clinicians, as well as guarantee to these patients the most appropriate clinical management, avoiding unnecessary and/or disproportionate treatments.